Effect of Reinforcement Particle size on the properties of Dispersion Strengthened Al-SiC - Zuhailawati Hussain (Kolej Universiti Kejuruteraan Utara Malaysia, 2008)
Link to publisher's homepage at http://www.unimap.edu.my/